Importance of Dalk (massage) in Neurodisorders- Unani Perspective - Farzana, M.U.Z.N.; Sultana, A. (Hazrat Ghouse ul Azam Academy; Unani Medical Association, India, 2017)
In Unani system of medicine, dalk (massage) has been used for the preventive and as well as therapeutic indications since the time of antiquity. In Unani system of medicine, simulates with massage; it is a form of riyazat (exercise) under taken by hands as a manipulative technique over the muscles to produce hararat (heat), hence causing tahallul (dissolvent) and riqqat (liquidity) in fuzlat (morbific matter). It also strengthens the autar (ligaments) va azlat (muscles) and evacuates the fuzlah of hazm akheer (waste metabolites of the body. The mechanism of action of dalk is based on two basic concepts i.e. Tanqiya-e-Mawad (elimination of morbid matter) and Imala-e-Mawad (diversion of morbific matter). A number of Unani physicians recommended dalk as preventive as well as curative measure. In neurodisorders dalk provides very good response. Dalk timing, duration, its types and importance, mechanism of action, recent scientific reports in neurodisorders in which massage can be used have been discussed in this paper.
Keywords: fuzlat; neurodisorders; Tanqiya-e-Mawad; Imala-e-Mawad